Pengaruh Persekitaran Tempat Kerja Terhadap Pemindahan Pembelajaran Di Organisasi: Kajian Kes Bagi Program Latihan Yang Berasaskan Komputer Di Universiti Malaysia Sarawak (UNIMAS) - Angielia R., Rentap (Universiti Malaysia Sarawak (UNIMAS), 2005)
Currently, the organization more focuses on the effectiveness of learning transfer to the job performance compared to the cost and design of learning (or training) programs. This research explores the influences of work environment factor on the learning transfer in computer based training programs. Generally, the research objectives were to (1) determine the differences in level of learning transfer in the computer based training programs by demographic variables, (2) determine the relationship between work environment factors and learning transfer in computer based training programs and (3) determine the level of learning transfer in computer based training programs. The work environment factors such as management support, peer support, technological support and organization climate and culture were included in this research. Meanwhile, demographic factors such as gender, age and period of duty also included. The research scope covers the support staffs at University Malaysia Sarawak (UNIMAS). 62 respondents, representing the 11% of population were randomly selected. The findings showed that (1) there were no significance differences among all demographic factors (such as gender, age and period of duty) and level of learning transfer in the organization, (2) there were significance relationship between all work environment factors (such as management support, peer support, technological support and also organizational climate and culture) and learning transfer in the computer based training programs and (3) most of respondents (82.3%) have a positive learning transfer in computer based training programs. Based on this research, it is concluded that it is important to take work environment factors into account when considering support for transfer of learning from computer based training programs back to the workplace.